On being despised: growing up a Congolese refugee in Dar es Salaam - Mann, G (Palgrave Macmillan, 2012)
Young Lives has been introduced as a longitudinal study that follows two cohorts of children in poor communities in Ethiopia, India, Peru and Vietnam as they grow into young adults. In this chapter, after pointing to the importance of longitudinal studies in the social sciences, we use the experience of designing and implementing Young Lives to reflect on some issues surrounding the process of such studies, and on the use of their findings to inform policy.